Preparation method of nickel ammonium phosphate negative electrode material

The preparation of floral nickel ammonium phosphate electrode material through microwave digestion method solves the problem of long reaction time during the preparation process of nickel ammonium phosphate, and achieves efficient and stable electrochemical performance. It is suitable for the negative electrode material of supercapacitors.

CN119240639APending Publication Date: 2025-01-03SHANXI INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411160016.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-22
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The reaction time of nickel ammonium phosphate during the preparation process is long, limiting its possibility in large-scale applications.

Method used

The diammonium hydrogen phosphate and nickel source were dissolved in deionized water by microwave digestion method, and then the urea was added to carry out microwave digestion reaction, followed by washing with distilled water and ethanol and drying to prepare a flower-like nickel ammonium phosphate electrode material.

Benefits of technology

It realizes a fast and convenient preparation process, high yield, high material with high conductivity, stability and excellent electrochemical properties, and is suitable for negative electrode materials of supercapacitors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119240639A_ABST
    Figure CN119240639A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of electrode materials, and discloses a method for microwave preparation of a flower-like nickel ammonium phosphate negative electrode material, and the method specifically comprises the following steps: S1, dissolving diammonium hydrogen phosphate and a nickel source in deionized water to obtain a solution; s2, adding urea into the solution in the S1, and stirring; s3, transferring the solution treated in S2 into a reaction kettle of a microwave digestion instrument, and carrying out microwave digestion reaction; and S4, centrifuging the product obtained in S3 by using distilled water and ethanol in sequence, washing and drying. The novel method for preparing the nickel ammonium phosphate electrode material by using the microwave digestion instrument provided by the invention is rapid and convenient, and relatively high in yield; and the nickel ammonium phosphate electrode material with more stable structure, high conductivity, high stability and excellent electrochemical performance can be prepared by controlling reaction conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrode materials, and in particular to a method for preparing a nickel ammonium phosphate negative electrode material and a supercapacitor negative electrode prepared by the method. Background Art

[0002] As a new type of energy storage device, supercapacitors have the advantages of high power density, long life, fast charging and discharging, and are widely used in electric vehicles, renewable energy and other fields. The performance of supercapacitors depends on the performance of electrode materials. Therefore, researching and developing high-performance electrode materials is the key to achieving breakthroughs in supercapacitor technology.

[0003] Ammonium / transition metal phosphate NH4MPO4, M=(Mn 2+ , Fe 2+ ,Co 2+ , Ni 2+ , Cu 2+ ) has been studied for more than 50 years and has been widely used as fertilizers, paint finish pigments to protect metals, and flame retardants in paints or plastics. However, there are currently a few studies that have established transition metal / ammonium phosphate-based materials as electrodes for supercapacitors. For example, Pang Huan et al. used NH4CoPO4·H2O synthesized by a hydrothermal method and performed three-electrode and two-electrode measurements on the samples using 3M KOH aqueous electrolyte. In the two-electrode, graphene nanosheets are used with NH4CoPO4·H2O as the positive electrode to form an NH4CoPO4·H2O microbeam-graphene nanosheet asymmetric device. At 1.5Ag -1 The current-asymmetric device shows a maximum specific energy of 26 Whkg -1 Corresponding specific power 788Wkg -1 NH4Co synthesized by Peng Xiao et al. x Ni 1-x PO4·H2O nanostructures were synthesized by a simple one-step solvothermal method. The synthesized materials were assembled with activated carbon in an asymmetric device with a specific energy of 37.5 Whkg -1 Corresponding specific power 826W kg -1 It has a potential window of 0-65 V in 3M KOH.

[0004] These ammonium / transition metal phosphate materials have unique advantages over other materials, such as abundant active sites and fast interfacial transport of charge carriers by reducing the diffusion paths of ions. In addition, these materials have strong PO covalent bonds, which makes them very stable in structure and chemical properties. In supercapacitor applications, short diffusion path lengths for charge carriers and chemically stable structures of electrodes are very important.

[0005] As a representative of ammonium / transition metal phosphates, nickel ammonium phosphate (NiNH4PO4) is a new type of electrode material with high conductivity, excellent energy storage performance and good chemical stability. It is considered to be a negative electrode material for supercapacitors with broad application prospects. However, the preparation process of nickel ammonium phosphate generally adopts ultrasonic dispersion and hydrothermal heating, and the reaction time is long, which limits its possibility in large-scale application. Therefore, it is urgent to develop a new method for preparing nickel ammonium phosphate material. Summary of the invention

[0006] In order to overcome the above-mentioned defects, the present invention provides a method for preparing a flower-shaped nickel ammonium phosphate negative electrode material, comprising:

[0007] S1: dissolving diammonium hydrogen phosphate and a nickel source in deionized water to obtain a solution;

[0008] S2: adding urea to the solution described in S1 and stirring;

[0009] S3: transferring the treated solution in S2 to the reaction vessel of a microwave digestion apparatus to perform microwave digestion reaction;

[0010] S4: The product obtained in S3 is centrifuged, washed and dried with distilled water and ethanol in sequence.

[0011] Furthermore, the nickel source described in step S1 is nickel chloride, nickel nitrate or nickel acetate, the molar ratio of the diammonium hydrogen phosphate to the nickel source is 3-4:1, and the amount of the deionized water to the nickel source is 1 mL: 0.5-0.7 mmol.

[0012] Furthermore, in step S2, the ratio of the amount of urea added to the amount of the nickel source is 1-1.2:1, and the stirring time is 5-15 minutes.

[0013] Furthermore, in step S3, the microwave digestion reaction temperature is 150±10° C., and the microwave digestion reaction time is 30-150 minutes.

[0014] Furthermore, the drying apparatus used in step S4 is a constant temperature drying oven, the drying temperature is 60±10° C., and the drying time is 10-15 hours.

[0015] Another aspect of the present invention provides a flower-shaped nickel ammonium phosphate negative electrode material prepared by the above method.

[0016] The XRD spectrum of the nickel ammonium phosphate crystal has a sharp peak shape, a narrow half-peak width, no redundant diffraction peaks such as phosphite or phosphate, and has high purity and crystallinity.

[0017] The ammonium nickel phosphate crystals have multiple and uniformly dispersed micrometer-level layered structures; further, the ammonium nickel phosphate crystals have a flower-like structure; further, the ammonium nickel phosphate crystals are formed by multiple rectangular sheets being assembled in stages in all directions.

[0018] The ammonium nickel phosphate crystals have a length of 20-40 microns, a width of 10-20 microns, and a thickness of 2.5-3.5 microns.

[0019] A third aspect of the present invention provides a method for preparing a nickel ammonium phosphate electrode, comprising:

[0020] S1: mixing the nickel ammonium phosphate active material, acetylene black and polytetrafluoroethylene in a mass ratio of 80-85:10-15:5 to obtain a black paste;

[0021] S2: Apply the black paste mixed with S1 onto a 10mm×15mm nickel foam;

[0022] S3: The working electrode is formed by pressing at a pressure of 10 MPa for 60 seconds using a tablet press, and then transferred to an oven for drying for 24 hours.

[0023] A fourth aspect of the present invention also provides a lithium battery comprising the above-mentioned negative electrode material.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] 1. The present invention provides a simple and efficient new method for preparing nickel ammonium phosphate electrode material using a microwave digestion instrument. The method is fast and convenient, has a high yield, and the synthesized material has good electrochemical properties;

[0026] 2. The present invention utilizes a novel preparation process of microwave digestion to control the reaction conditions, and the prepared ammonium nickel phosphate electrode material has a more stable structure, high conductivity, high stability and excellent electrochemical properties, and can be used as an excellent negative electrode material for supercapacitors. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for use in the description of the embodiments of the present invention will be briefly introduced below. Obviously, the accompanying drawings in the following description are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative labor.

[0028] Figure 1 The nickel ammonium phosphate powder prepared in Example 1-3;

[0029] Figure 2The X-ray diffraction pattern of the ammonium nickel phosphate prepared in Example 1;

[0030] Figure 3 This is the electron microscope scanning spectrum of the nickel ammonium phosphate prepared in Example 1;

[0031] Figure 4 The cyclic voltammogram of the nickel ammonium phosphate prepared in Example 1;

[0032] Figure 5 This is a comparison diagram of the electrochemical performance of ammonium nickel phosphate prepared in Example 1 at different current densities;

[0033] Figure 6 The AC impedance curve of the nickel ammonium phosphate prepared in Examples 1-3. DETAILED DESCRIPTION

[0034] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention clearer, the present invention is further described in detail below in conjunction with the embodiments and drawings. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. The present invention is specifically introduced below in conjunction with the specific embodiments.

[0035] The embodiment of the present invention provides a method for preparing a flower-shaped ammonium nickel phosphate negative electrode material by microwave, comprising:

[0036] S1: dissolving diammonium hydrogen phosphate and a nickel source in deionized water to obtain a solution;

[0037] S2: adding urea to the solution described in S1 and stirring;

[0038] S3: transferring the treated solution in S2 to the reaction vessel of a microwave digestion apparatus to perform microwave digestion reaction;

[0039] S4: The product obtained in S3 is centrifuged, washed with distilled water and ethanol, and dried.

[0040] The preparation of the negative electrode material of the present invention adopts the method of microwave heating, wherein microwave heating is affected by the properties of the target material and the degree of its interaction with microwaves, and the properties of the target material play a major role. Common microwave interaction phenomena include reflection, absorption and transmission. Common microwave reflectors are usually electrical conductors, such as metals, which do not absorb microwaves and therefore cannot be heated. Microwave absorption is mainly aimed at polar liquids. When microwaves are irradiated, different dipoles and ions in polar liquids interact with electromagnetic waves and conduct ions. In this process, energy loss is generated due to the collision between ions and dipoles. This part of energy is released in the form of heat and diffuses inside the material.

[0041] The microwave heating method is different from the traditional heating method. The traditional heating is carried out through conduction and convection, and transfers heat from the surface to the internal molecules. This is a transmission process from the outside to the inside. Microwave heating is a method of heating from the inside to the outside, which allows the material to be heated more evenly and quickly. On the other hand, energy loss is inevitable during the energy transfer process, but the direct interaction of microwave heating reduces this energy consumption. In general, microwave heating can heat materials more quickly and evenly, reduce energy consumption, and is economical and effective.

[0042] Furthermore, the nickel source described in step S1 is nickel chloride, the molar ratio of the diammonium hydrogen phosphate to the nickel source is 3-4:1, and the amount of the deionized water to the nickel source is 1 mL: 0.5-0.7 mmol.

[0043] The purpose of adding excess diammonium hydrogen phosphate is to completely consume the nickel source and reduce the generation of heavy metal waste liquid.

[0044] Furthermore, in step S2, the ratio of the amount of urea added to the amount of the nickel source is 1-1.2:1, and the stirring time is 5-15 minutes.

[0045] Furthermore, in step S3, the microwave digestion reaction temperature is 150±10° C., and the microwave digestion reaction time is 30-150 minutes.

[0046] Furthermore, the drying apparatus used in step S4 is a constant temperature drying oven, the drying temperature is 60±10° C., and the drying time is 10-15 hours.

[0047] Another aspect of the present invention provides a flower-shaped nickel ammonium phosphate negative electrode material prepared by the above method.

[0048] The XRD spectrum of the nickel ammonium phosphate crystal has a sharp peak shape, a narrow half-peak width, no redundant diffraction peaks such as phosphite or phosphate, and has high purity and crystallinity.

[0049] The ammonium nickel phosphate crystals have multiple and uniformly dispersed micrometer-level layered structures; further, the ammonium nickel phosphate crystals have a flower-like structure; further, the ammonium nickel phosphate crystals are formed by multiple rectangular sheets being assembled in stages in all directions.

[0050] The ammonium nickel phosphate crystals have a length of 20-40 microns, a width of 10-20 microns, and a thickness of 2.5-3.5 microns.

[0051] The third aspect of the present invention also provides a lithium battery comprising the above-mentioned negative electrode material.

[0052] The following is explained in conjunction with specific embodiments:

[0053] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, etc. used in the following examples are all commercially available unless otherwise specified, and the techniques not described in detail are all performed according to standard methods well known to those skilled in the art.

[0054] Example 1

[0055] Preparation of flower-like nickel ammonium phosphate powder 1:

[0056] S1: dissolving 27 mmol of diammonium hydrogen phosphate and 9 mmol of nickel chloride in 15 mL of deionized water to obtain a solution;

[0057] S2: Add 9 mmol of urea to the above prepared solution and continue stirring for about 10 minutes;

[0058] S3: The stirred solution was transferred to the reaction vessel (20 mL) of the microwave digestion apparatus and reacted at 150°C for 30 min;

[0059] S4: The product prepared in S3 was centrifuged and washed three times with distilled water and ethanol respectively, and finally dried in a constant temperature drying oven set at 60° C. for 12 hours. The final product was 2.58 g, with a yield of 70%.

[0060] Example 2

[0061] Preparation of flower-like nickel ammonium phosphate powder 2:

[0062] The microwave digestion reaction time in step S3 is 90 min, and the remaining steps are the same as those in Example 1.

[0063] Example 3

[0064] Preparation of flower-like nickel ammonium phosphate powder 3:

[0065] The microwave digestion reaction time in step S3 is 150 min, and the remaining steps are the same as those in Example 1.

[0066] The actual picture of the nickel ammonium phosphate powder prepared in Example 1-3 is as follows Figure 1 shown.

[0067] The nickel ammonium phosphate powder prepared in Examples 1-3 was tested:

[0068] X-ray diffraction analysis

[0069] The inventors conducted an X-ray diffraction experiment on the nickel ammonium phosphate electrode material prepared in Example 1. Figure 2The diffraction peaks of the electrode material prepared in Example 1 are shown, which are basically consistent with the diffraction peaks of the nickel ammonium phosphate standard card (JCPDS NO.50-0425), indicating that the electrode material prepared by us is nickel ammonium phosphate crystal. In addition, it can be seen from the XRD of nickel ammonium phosphate that its peak shape is sharp, the half-peak width is narrow, and there are no other redundant diffraction peaks, such as phosphite or phosphate, indicating that the NH4NiPO4·H2O material prepared under our experimental conditions has high purity and good crystallinity.

[0070] Microscopic morphology detection

[0071] Figure 3 a is a typical low-magnification image of sample c30 of Example 1, from which it can be clearly seen that the synthesized material is a multi-micrometer-level layered structure that is uniformly dispersed. Figure 3 f is a picture of the sample of Example 1 taken under a high magnification scanning electron microscope, which further obtains more detailed results about the size of a single electrode material. From the picture taken at a low scanning electron microscope magnification, it can be obtained that the length of a single sample material prepared at a microwave of 30 minutes is about 20-40 microns, the width is about 10-20 microns, and the average thickness is about 2.5-3.5 microns. From the high-power microscope scanning picture, the detailed morphology of the prepared sample can be seen, which is composed of many rectangular pieces assembled together in various directions.

[0072] The inventors also prepared nickel ammonium phosphate electrodes and tested their performance.

[0073] The preparation method of the nickel ammonium phosphate electrode is as follows: the nickel ammonium phosphate active material, acetylene black and polytetrafluoroethylene are mixed together in a ratio of 80:15:5, and then the mixed coating is evenly applied to a 10mm×15mm nickel foam, and finally a tablet press is used to press for 60s under a pressure of 10MPa to form a working electrode, and then the electrode is transferred to an oven for drying for 24h.

[0074] The performance test was carried out in a three-electrode system, using a saturated calomel electrode as a reference electrode and a platinum electrode as a counter electrode (i.e., an auxiliary electrode). The entire test system was completed in a 3M potassium hydroxide (KOH) electrolyte. All electrochemical tests were completed using a CHI660E electrochemical workstation and a blue battery tester.

[0075] Cyclic voltammetry detection

[0076] The cyclic voltammogram of the sample of Example 1 is as follows: Figure 4As shown. It can be clearly seen that as the scan rate of cyclic voltammetry continues to increase, the corresponding redox current is also gradually increasing, indicating that ions and electrons can be quickly transferred between the electrode material and the electrolyte.

[0077] Electrochemical performance testing

[0078] The electrochemical performance of the nickel ammonium phosphate samples prepared in Examples 1-3 was tested, and the results are as follows: Figure 5 The inventors conducted a series of electrochemical performance tests on nickel ammonium phosphate samples with different current densities (1A, 2A, and 3A) by constant current charge and discharge. The charge and discharge specific capacitance test results were basically consistent with the specific capacitance results of the cyclic voltammetry test. By changing the current density from 1Ag -1 Increase to 3Ag -1 By calculating the specific capacitance of the samples in Examples 1-3: the specific capacitance of the sample in Example 1 (30 min) is 677.82 F / g, the specific capacitance of the sample in Example 2 (90 min) is 647.72 F / g, and the specific capacitance of the sample in Example 3 (150 min) is 522.32 F / g. It can be seen that the nickel ammonium phosphate electrode material prepared under the microwave reaction time of 30 min exhibits better rate performance than the nickel ammonium phosphate prepared with other reaction times. It is also found that the nickel ammonium phosphate prepared under the reaction time of 30 min has the best electrochemical performance.

[0079] Electrical impedance test

[0080] In order to explore the electron transfer ability and ion diffusion ability of nickel ammonium phosphate electrode materials, the inventors conducted an electrical impedance test on the prepared nickel ammonium phosphate electrode material. Figure 6 The nickel ammonium phosphate electrode material is shown from 5*10 -3 Hz to 10 4 Impedance spectrum in the Hz frequency range.

[0081] The impedance curve is composed of a straight line in the low-frequency region and a semicircle in the high-frequency region. The slope of the Nyquist curve in the low-frequency region can be used to represent the Warburg diffusion impedance. The slope is inversely proportional to the impedance. The larger the slope, the smaller the impedance. In addition, the radius of the semicircle in the high-frequency region can be used to represent the charge transfer resistance (Rct). The radius is proportional to the resistance. The smaller the radius, the smaller the resistance. It can be seen from the figure that in the high-frequency region, the semicircle diameter of the 30-min curve is smaller, which indicates that the charge transfer resistance (Rct) at the electrode-electrolyte interface of the microwave 30-min sample and the microwave 90-min sample is lower than that of the microwave 150-min sample, thereby obtaining better capacitance performance and a higher rate of redox reaction. In the low-frequency region, it can be seen that the straight line of the microwave 30-min sample is steeper than that of the microwave 90-min sample, with a higher slope, and the microwave 150-min sample is the worst, which indicates that the microwave 30-min sample has a shorter ion diffusion path than the microwave 90-min sample and the microwave 150-min sample, and the diffusion rate of ions from the electrolyte solution to the electrode surface will be faster.

[0082] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing flower-shaped ammonium nickel phosphate negative electrode material by microwave, comprising: S1: dissolving diammonium hydrogen phosphate and a nickel source in deionized water to obtain a solution; S2: adding urea to the solution described in S1 and stirring; S3: transferring the treated solution in S2 to the reaction vessel of a microwave digestion apparatus to perform microwave digestion reaction; S4: The product obtained in S3 is centrifuged, washed and dried with distilled water and ethanol in sequence.

2. The method for preparing flower-shaped ammonium nickel phosphate negative electrode material by microwave according to claim 1, characterized in that: The nickel source described in step S1 is nickel chloride, nickel nitrate or nickel acetate, the molar ratio of the diammonium hydrogen phosphate to the nickel source is 3-4:1, and the amount of the deionized water to the nickel source is 1 mL: 0.5-0.7 mmol.

3. The method for preparing flower-shaped ammonium nickel phosphate negative electrode material by microwave according to claim 1, characterized in that: In step S2, the ratio of the amount of urea added to the amount of the nickel source is 1-1.2:1, and the stirring time is 5-15 minutes.

4. The method for preparing flower-shaped ammonium nickel phosphate negative electrode material by microwave according to claim 1, characterized in that: The microwave digestion reaction temperature in step S3 is 150±10° C., and the microwave digestion reaction time is 30-90 minutes.

5. The method for preparing flower-shaped ammonium nickel phosphate negative electrode material by microwave according to claim 1, characterized in that: The drying in step S4 is performed using a constant temperature drying oven, the drying temperature is 60±10° C., and the drying time is 10-15 hours.

6. Flower-shaped nickel ammonium phosphate negative electrode material prepared according to the method of claims 1-5.

7. The flower-shaped nickel ammonium phosphate negative electrode material according to claim 6, characterized in that: The nickel ammonium phosphate has a length of 20-40 microns, a width of 10-20 microns, and a thickness of 2.5-3.5 microns.

8. A method for preparing a nickel ammonium phosphate electrode, using the flower-shaped nickel ammonium phosphate negative electrode material as claimed in claim 6 or 7, comprising: S1: mixing the nickel ammonium phosphate active material, acetylene black and polytetrafluoroethylene in a mass ratio of 80-85:10-15:5 to obtain a coating; S2: Apply the mixed coating in S1 to a 10mm×15mm nickel foam; S3: The working electrode is formed by pressing at a pressure of 10 MPa for 60 seconds using a tablet press, and then transferred to an oven for drying for 24 hours.

9. A lithium battery comprising the negative electrode material according to claim 6 or 7.